Impact of Vaccination, Insecticide-Impregnated Collar, and Treatment on the Canine Leishmaniasis - Esteva, L.; Ferreira, C. P.; Vargas, C. (Trends in Computational and Applied Mathematics, 2023)
Leishmaniasis is a parasite disease transmitted by the bites of sandflies.  There have been found more than 70 animal species that are natural reservoir hosts of Leishmania. Among the reservoirs, dogs are the most important ones due to their proximity to the human habitat. In this work, we formulate a model to assess the impact of vaccination, insecticide-impregnated collar use, and treatment on the control of canine leishmaniasis. To this end, we calculated the Basic Reproduction Number of the disease and carried out a sensitivity analysis of this parameter concerning the epidemiological and demographic parameters. The numerical simulations show the correlation between the disease prevalence and the strategies' effectiveness.  Control of infection on dogs can be obtained by protecting around 35 percent of dogs with vaccination and insecticide-impregnated collar.